Kontribusi Teori Sanksi dan Asas Pembuktian terhadap JarÃ®mah Korupsi di Indonesia - Nasrullah, Nasrullah (Program Pascasarjana UIN Sunan Ampel Surabaya, 2015)
Islamic law consists of a set of norms, principles and rules of law enforcement, dealing with the eradication of corruption. In the history of Islamic law, there have been the theories and principles of Islamic law, such as the theory of jawÃ¢bir, zawÃ¢jir, and the principle of min ayn lak hÃ¢dhÃ¢ (known as the reversed evidence) regarding the application of criminal sanctions of corruption. The application of criminal sanctions of corruption in Indonesia, especially with regard to the principle of reversed evidence has not been well-formulated. For the perfection of legislation in combating corruption, it is possible for the Indonesian government to amend the existing legislation, in order to make the country free from corruption. This paper focuses on the study of theoretical contributions on sanctions and the principle of proof evidence in Islamic criminal law to be transformed into criminal sanctions of corruption in Indonesia, which refers to the theory of jawÃ¢bir, zawÃ¢jir, and the principle of min ayn lak hÃ¢dhÃ¢, which had been done previously by the caliph âUmar b. al-KhattÃ¢b and succeeded in preventing and combating corruption.